Memory in ancient Rome and early Christianity - Galinsky, Karl; Galinsky, Karl (Oxford University Press, 2016)
'Memory in Ancient Rome and Early Christianity' presents perspectives from an international and interdisciplinary range of contributors on the literature, history, archaeology, and religion of a major world civilization, based on an informed engagement with important concepts and issues in memory studies